2018
DOI: 10.22478/ufpb.1807-8214.2018v25n1.36187
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres, tempos e espaços na ciência agropecuária paulista

Abstract: Este artigo olha para mulheres de diferentes tempos e a conquista por espaços na ciência agropecuária paulista. Neste sentido, tem como objetivo principal verificar a relação entre atributos sociodemográficos e o desenvolvimento da carreira de pesquisadoras lotadas em instituições públicas de pesquisa paulistas, no contexto do agronegócio. Para tanto, fez-se uso do aporte teórico-metodológico da demografia organizacional e dos estudos de gênero e geração nas ciências. O banco de dados sociodemográfico foi conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
2
2
0
1
Order By: Relevance
“…Concerning advancement to managerial positions, the results show that female graduates' access to these spaces is restricted: of the 15%, 10% are in technical management and 5% in administrative management. This conclusion is similar to those of Borges et al (2021), Serra (2018), andPereira et al (2011), who found that although the number of women in the agribusiness sector has increased, the number of men, especially in management positions, is higher. This indicates that the "glass ceiling," as pointed out by Oliveira and Serra (2018), persists in agribusiness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Concerning advancement to managerial positions, the results show that female graduates' access to these spaces is restricted: of the 15%, 10% are in technical management and 5% in administrative management. This conclusion is similar to those of Borges et al (2021), Serra (2018), andPereira et al (2011), who found that although the number of women in the agribusiness sector has increased, the number of men, especially in management positions, is higher. This indicates that the "glass ceiling," as pointed out by Oliveira and Serra (2018), persists in agribusiness.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is similar to those of Borges et al (2021), Serra (2018), andPereira et al (2011), who found that although the number of women in the agribusiness sector has increased, the number of men, especially in management positions, is higher. This indicates that the "glass ceiling," as pointed out by Oliveira and Serra (2018), persists in agribusiness.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Dentre os setores ocupados majoritariamente por homens, merece destaque o agronegócio. Há alguns estudos sobre a atuação de mulheres neste setor (Borges et al, 2021;Menezes & Silva, 2016;Oliveira & Serra, 2018;Pereira et al, 2011;Silva & Redin, 2020;Szöllösi & Dias, 2017), no entanto, não se observa neles um aprofundamento do debate sobre a desigualdade de gênero. Dentre os poucos estudos que abordam essa questão, pode-se citar o de Szöllösi e Dias (2017), que abordaram a trajetória profissional de mulheres agrônomas, identificando desigualdade de gênero.…”
Section: Introductionunclassified